Design of a liquid crystal beam-steerable antenna with characteristic mode analysis - Shu, Jun (2022)
A novel liquid crystal beam-steerable antenna is presented. It is a conventional liquid crystal microstrip patch antenna with a bending slot in the middle of the H-plane. Owing to the introduction of the bending slot, this antenna can work at even mode and odd mode within a frequency band. To obtain the resonant frequencies and radiation characteristics of the two modes, the method of characteristic mode analysis is utilised. It indicates that the resonant frequency of even mode is lower than that of odd mode. Therefore, by choosing liquid crystal as its substrate, this antenna can alter its operating modes by varying the permittivity of liquid crystal. Furthermore, beam steering can be realised since the radiation patterns of the two modes are divergent. An antenna prototype at Ka-band has been designed, fabricated and measured. The measured results show that the maximum radiation direction can scan from −30° to −2° continuously at 26.5 GHz in the H-plane.